Nowoczesne technologie informacyjno-telekomunikacyjne przyczyną dyskryminacji rynkowej - Frąckiewicz, Ewa (Information and communication technology as a source of customer discrimination, 2006)
In the modern economy, the information takes strategic role in an enterprise. On the other hand, the information describes customer position. The style of adoption of new technology determines his market power. Not all consumers adopt information and communication technology (ICT) in the same way. It is a case of new discrimination - an enterprise treats clients in the different way by their knowledge, experience and ability to learn. This differentiation can be a result of different costs, but ignores adopting possibilities of consumers. The current paper presents a new approach for segmenting adopter categories in the ICT market and three sources of market discrimination: knowledge, competence and confusion of customer.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1134, s. 196-204